Implicit causality: When more than one explanation is missing - Israel de la Fuente; Marie Benzerrak; Natalia Kalashnikova; Lala Naziyeva; Ching-chun Wang; Barbara Hemforth (2017)
It has been shown that focus particles like “only” and “even” give way to a pattern of pronoun production and resolution similar to what has been observed with implicit causality verbs like “criticize” or “annoy” in (1) where so-called N1-biased verbs like “annoyed” systematically provoke explanations related to the subject (Peter) and N2-biased verbs like “criticized” continuations related to the object (Mary). Peter annoyed/criticized Mary because .. Continuation studies with sentences like (2), using unbiased verbs show that an antecedent in the scope of “only” similarly systematically attracts continuations while an antecedent in the scope of “even” is systematically dispreferred. Only/Even Peter called Mary because … Following Bott and Solstad (2014), we argue that focus particles as well as IC verbs, when combined with discourse connectives like because, create expectations for an explanation about the ensuing discourse that needs to be filled to avoid the accommodation of missing information. These explanations, which reflect the relationship between the focus entity in the scope of the particle and the set of alternatives related to it, introduce a bias for one of the two potential antecedents. “Only” triggers a missing explanation of exclusivity: why does only Peter call and nobody else. “Even”, on the other hand, triggers an explanation of the unlikeliness of Peter calling, what it is about Mary that makes even him call. An obvious and still open question is what happens when we combine biased verbs with focus particles thus provoking matching or mismatching expectations. We expected that matching biases (even N1 + N2-biased verb; only N1 + N1-biased verb) where the focus particle and the verb bias demand an explanation related to the same antecedent should provoke the strongest biases since a single explanation can easily be found to fill discourse needs (e.g. “Only Peter fascinates Mary because he is just the best.”, “Even Peter criticized Mary because she really messed up this time.”). In mismatching cases (even N1 + N1-biased verb; only N1 + N2-biased verb), only one of the missing explanations can easily be provided. In (3) we can either explain exclusivity (… because he is never satisfied) or the N2-bias of the verb (… because she had messed up.). Only Peter criticized Mary because … We ran a continuation study in French with 10 N1-biased verbs (4), 10 N2-biased verbs (5), and 10 verbs without bias (6), taken from a recently established corpus of implicit causality biases including 320 French verbs. We constructed preambles with two gender-different proper names with the subject in the scope of “seul” or “même” (following a Latin Square Design). 84 native French speakers provided continuations to the preambles. All preambles ended with “parce qu’”, strongly encouraging a pronoun continuation (only words with initial vowels can follow “qu’”, “il”/he and “elle”/she thus become highly likely). In logistic regressions, both, focus particles as well as the IC-bias of the verb showed a significant effect (FP: z= 4.471, p<.001; IC-bias: N1/N2: z= -8.932, p<.001; N1/no-bias: z= -4.329, p<.001). As expected, matching cases showed a very strong bias (Only+N1-bias = 79% N1; Even+N2-bias: 81% N2), while mismatching cases were more varied. N1-bias Seul/Même Marie enchante Adrien parcqu’ …       Only/Even Mary enchants Adrian because … N2-bias       (5) Seul/Même Pierre félicite Auriane parce qu’ …            Only/Even Peter congratulates Auriane because … No-bias Seul/Même  Pierre interroge Marie parce qu’ …        Only/Even  Peter visits Marie because …